Mandibular first and second molar tooth transposition: a case report - J. E. R. GRANT, N. ABU MEZIER, & A. T. DIBIASE (Paediatric Dentistry, 2006)
A case is reported of what appears to be a transposition affecting the mandibular first, second, and third molars.